2020
DOI: 10.15557/jou.2020.0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the resistive indices obtained in the uterine artery and the ophthalmic artery in preeclamptic and normotensive patients in Doppler US

Abstract: Introduction Preeclampsia is a medical condition characterized by hypertension and proteinuria during pregnancy, with the symptoms generally manifesting in the 3 rd trimester. Hypertension brings hemodynamic changes; it is therefore expected that arterial blood flow velocity waveforms will be different in the uterine and ophthalmic arteries in preeclampsia. Vascular changes do occur in preeclampsia, which in turn induces hemodynamic changes. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…In seven studies evaluated, the mean RI difference for overall PE was -0.07 (95% CI -0.09; -0.04), I2 = 81% with cut-offs established by the primary studies of 0.62 15 , 0.64 16 , 0.66 12,17 , 0.67 18 , 0.68 13,30 (Supplement 8). In the mild PE group there were seven studies with mean difference of -0.02 (95% CI -0.14; 0.09), I2 = 99% with cut-offs of 0.63 31 , 0.641 4 , 0.66 15 , 0.73 32,33 , 0.77 11 , 0.97 19 (Supplement 9).…”
Section: Resistance Index (Ri) and Pulsatility Index (Pi)mentioning
confidence: 97%
See 2 more Smart Citations
“…In seven studies evaluated, the mean RI difference for overall PE was -0.07 (95% CI -0.09; -0.04), I2 = 81% with cut-offs established by the primary studies of 0.62 15 , 0.64 16 , 0.66 12,17 , 0.67 18 , 0.68 13,30 (Supplement 8). In the mild PE group there were seven studies with mean difference of -0.02 (95% CI -0.14; 0.09), I2 = 99% with cut-offs of 0.63 31 , 0.641 4 , 0.66 15 , 0.73 32,33 , 0.77 11 , 0.97 19 (Supplement 9).…”
Section: Resistance Index (Ri) and Pulsatility Index (Pi)mentioning
confidence: 97%
“…Five studies had uncertain risks in the patient selection and ow and timing domains. 11,30,31,32,33 The study by Madina et al 16 scored low and risk of bias in the assessment of applicability concerns involving the index and standard tests, as it did not specify how pregnant women were allocated or the parameters used to de ne preeclampsia in the methodology.…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…full-text review of the remaining 13 articles led us to identify 8 observational studies that met the inclusion criteria, comprising 640 pregnant women with or without confirmed preeclampsia. [13][14][15][16][17][18][19]25,34 Details on the literature search are displayed in Figure 1. Five case-control and 3 cross-sectional studies were enrolled.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…13 The value of ophthalmic artery Doppler parameters as predictive tools for preeclampsia recently have assessed by an increased number of studies, however, the results are heterogeneous, and no clear consensus has been achieved regarding their exact role in clinical practice. [13][14][15][16][17][18][19][20][21][22][23][24][25] The aim of this meta-analysis was to investigate the potential significance of ophthalmic Doppler parameters in preeclamptic women and to provide evidence-based hints for both clinical practice and scientific investigation.…”
Section: Introductionmentioning
confidence: 99%